Application of Profiling in Security Systems of Critical Infrastructure Objects - Lukin, Sergiy; Tikhonenko, Oleksandr (Theory and Practice of Public Administration, 2024)
The article offers the author’s vision of the possibility and effectiveness of applying modern scientific methods in systems for ensuring the safety of important objects of various forms of ownership, including objects of critical infrastructure. The purpose of this article is to continue the study of profiling mechanisms in the field of identifying threats to state security. This field is especially critical in the context of global geopolitical changes that become prerequisites for increasing military, criminal, terrorist and other threats. The author also considers the concept of safety as a state and process and highlights the actual need for finding and developing effective practical methods to achieve such a state. Profiling as a method for predicting the behavior of the anthropogenic type of threats to the offender and related events is an essential practical tool in the arsenal of the ultimate executor — the security officer. The article examines the theoretical and practical basis of implementation in practical processes of ensuring the security of an object of critical infrastructure in conditions of increased military risks. The author considers ways of integrating profiling with other technologies for ensuring physical security, including modern video surveillance systems, access control and management, artificial intelligence and others. It is shown that effective provision of physical security requires not only modern equipment of security systems and high qualification of end performers — employees able to respond quickly to threats. But also the creation of a certain environment in which the use of such equipment and employees will have the most productive level, while attracting the minimum necessary resources. On the basis of the conducted studies, it is concluded that it is necessary to develop a unified methodology and standards and protocols for the use of profiling in the construction of physical security systems for critical infrastructure facilities. This will increase the efficiency of detection and prevention of threats, minimize the level of risks to the civilian population, and ensure the stable functioning of critical facilities. Even in conditions of military instability, rational use of resources, forces, and means. Prospects for further research in the field of profiling and its integration with promising technologies aimed at improving the level of state security are considered.